The study of the analytical method of evaluating the probability of potential conflict situations in air traffic - Васильєв, В.M. (Proceedings of National Aviation University (archive), 2007)
Application of the method of potential conflicts probability evaluation offered before for air traffic control system is considered. The properties of the method are investigated, results of computer modeling are represented and analyzed.